Changes in L2 writers' self-reported metalinguistic knowledge of lexical phrases over one academic year. Issue 6 (1st November 2020) - Çandarlı, Duygu
ABSTRACT: Metalinguistic knowledge is regarded as an important factor in the development of writing. However, little attention has been paid to the metalinguistic knowledge of L2 writers in non-anglophone contexts. This study investigates L1-Turkish-speaking, first-year university students' metalinguistic knowledge of the lexical phrases they use in their own academic writing, in English at an English-medium university. Stimulated recall protocols were carried out with 10 participants at both the beginning of the first semester and the end of the second semester of their first year at university. The results show that the participants' self-reported metalinguistic understanding of lexical phrases tended to shift from low- and medium-level awareness to high-level awareness, although variability was found within the group. This study also provides evidence for a moderate negative correlation between the levels of metalinguistic knowledge and frequencies of lexical phrases in L2 writers' essays. The participants' metalinguistic understanding of lexical phrases seems to be shaped by their prior learning experiences and their conceptualisations of lexical phrases. This qualitative perspective provides new understandings into lexical phrases in academic writing, which would not be gained through only examining L2 writers' texts. The findings have implications for teaching English and academic writing in English-medium instruction contexts.